SCALE AND POSSIBILITIES OF RURAL DEVELOPMENT FINANCING THROUGH LAG - Brodziński, Zbigniew (Acta Scientiarum Polonorum. Oeconomia, 2010)
The objective of the paper is to point out possibilities and rural development support through LGD, based on the example of Leader group from Warmia and Mazury voivodeship. Results of documents describing conditions of the Community Support Framework 2007–2010 realization were presented within rural areas development. Moreover, based on the example of local activity group (LAG) from Warmia and Mazury voivodeship plans of funds directed for local strategies development (LSD) realization were presented. It was found that the amount of funds directed for LSD realization is relatively small (symbolic) in comparison to local needs. LAG by active looking for other than PROW finance source realization of LSD can be very important factor of economic and social development of rural areas.